Serological responses to IBR viral vaccine and Mannheimia haemolytica bacterin/leukotoxoid administered with needle-free injection technology - John F. Smith; B.J. Johnson; Sanjay Kapil; Larry C. Hollis; Derek A. Mosier (Kansas Agricultural Experiment Station Research Reports, 2005)
Yearling steers were randomized to treatment and vaccinated with 5-way modified live viral vaccine and Mannheimia haemolytica bacterin/toxoid by using either needle-free or standard needle injection. Blood samples were collected from all animals at the time of vaccination and 21 days later, and the serum was analyzed for antibody titers to infectious bovine rhinotracheitis (IBR) virus and M. haemolytica leukotoxoid. Serological responses to the IBR viral fraction of the 5-way viral vaccine were significantly greater on day 21 after administration with the needle-free injection system. Serological responses to the M. haemolytica leukotoxoid tended to be greater on day 21 after administration with the needle-free injection system.
Keywords: Cattlemen' s Day; 2005; Kansas Agricultural Experiment Station contribution; no. 05-144-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 943; Beef; Mannheimia haemolytica bacterin/leukotoxoid; IBR viral vaccine